Differential Neuroprotection of Selective Estrogen Receptor Agonists against Autonomic Dysfunction and Ischemic Cell Death in Permanent versus Reperfusion Injury - Barry J. Connell; Tarek M. Saleh (Advances in Pharmacological Sciences)
In the present study, we tested the hypothesis that selective activation of estrogen receptor subtypes (ERα and ERβ) would be neuroprotective following ischemia and/or ischemia-reperfusion, as well as prevent the associated autonomic dysfunction. The selective ERα agonist, PPT, when administered 30 min prior to occlusion of the middle cerebral artery (pMCAO), resulted in a dose-dependent neuroprotection as measured 6 hours postpermanent MCAO, but not following 30 mins of MCAO followed by 5.5 hrs of reperfusion (I/R). In contrast, 30 min pretreatment with the selective ERβ agonist, DPN, resulted in a dose-dependent neuroprotection following I/R, but was not protective following pMCAO. Both drugs prevented the ischemia-induced autonomic dysfunction as measured by a decrease in the baroreceptor reflex sensitivity (BRS). The data presented here suggest a differential role of each ER subtype in targeting the mechanisms of cell death that occur in ischemia versus reperfusion injury.